Exploring the Role of Human Endogenous Retroviral Gag in the Formation and Content of Extracellular Vesicles - McCulloch, Danielle (Université d'Ottawa / University of Ottawa, 2018)
Human Endogenous Retroviruses (HERV) are derived from exogenous retroviruses that infected inheritable germline tissues millions of years ago and account for 8% of the human genome. Like other retroviruses HERVs encode Gag, Pol and sometimes Env proteins. During a retroviral infection, retroviral Gag recruits the hosts Endosomal Sorting Complex Required for Transport (ESCRT) and associated proteins (ALIX and TSG101) to produce precisely sized viruses from endosomes or the plasma membrane. The ESCRT machinery is also involved in cytokinesis and control growth factor receptor signalling. HERV-K is the most recent HERV family to insert into the genome and is still able to produce mostly intact transcripts, including Gag. When expressed, Gag causes cells to release Virus-Like Particles (VLP) that lack HERV genomes. These retroviral VLP are remarkably similar to a sub-category of extracellular vesicles (EVs) called exosomes. Exosomes require ALIX, TSG101 and the ESCRT machinery for their production. It is possible that HERV-K Gag is required for exosome production or that HERV VLPs are a major contaminant of exosome preparations that account for many of the functions attributed to exosomes. Our data shows that HERV-K Gag over-expression or knockdown did not change the number of EVs released per cell in two cell lines. As well there was no difference in the amount of ALIX and TSG101 in the EVs in these conditions. The most intriguing observation made was the increase of cell number with expression of HERV-K Gag and decrease when HERV-K Gag was knocked down in HEK293T. We are currently unable to conclude the role of HERV-K Gag on EV production and content. We speculate that HERV-K Gag might affect cells through controlling cell proliferation or death, for example by competing with ESCRT machinery to impact signalling through growth factor receptors. This study begins to outline the potential effects HERV-K Gag might have on EV release and cell proliferation.
Keywords: HERV-K Gag; Extracellular Vesicles